Effects of florfenicol metaphylaxis in reducing morbidity and associated performance losses in stressed beef calves - Huck, G.L.; Stokka, Gerald L.; Marston, T.T.; Falkner, Thomas R. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
In February, 1998, 191 crossbred steers (885 lb) were used in a 28-day feeding trial to evaluate the effects of florfenicol (Nuflor®) on morbidity of newly weaned, lightweight cattle. No clinical signs of illness were observed in either the medicated or control group. No statistically significant differences in daily gain, feed intake, or feed efficiency were observed between treated and nontreated cattle.
Keywords: Beef; Nuflor®; Metaphylaxis; Intake; Morbidity; Receiving